Pemanfaatan Informasi Olahraga di Media Massa Cetak oleh Guru Pendidikan Jasmani dan Kesehatan dalam Pembelajaran Pendidikan Jasmani dan Kesehatan di SMA 5, SMA 6, SMA 11 Semarang - Muhaimin, Muhaimin (Universitas Semarang, 2011)
Utilization of information in mass media print by master of physical education and health in physical education and health in SMA 5, SMA 6, SMA 11 Semarang. The presence of print media is now a community needs. That's because, the print media presents a variety of information including information of actual politics, culture, economy, crime, entertainment, and sports. Basically, sports information in the print media have educational value and can add insight to a reading of new knowledge. The study produced these findings: (1) third physical education and health teacher at school who becomes the object research have made use of sports information in the print media to support the success of teaching and learning process, (2) the type of information they use to support the success of learning teaching is a form of news, articles about health, (3) form of utilization is appropriate to set clipping and through direct delivery of the material in the field while providing practice in the field. This method is considered more effective because all students can immediately practice, (4) sports information in the print media meets the needs of teachers and physical health education in supporting the learning process.